Three songs, no flash! : your ultimate guide to concert photography - Beerens, Loe (Rocky Nook ; Distributed by O'Reilly Media, 2010)
"Author Loe Beerens, a veteran photographer on the international concert scene, relates his experience in and knowledge of all the important aspects of planning and photographing concerts of all kinds. From punk to classical and everything in between, Loe covers how the music industry is organized, how to get access, the right people to befriend, and the proper etiquette of concert photography. From preparation to equipment selection, the reader will learn how to make the most of those three songs from this richly illustrated book. Shooting techniques for each of the major musical instruments are covered, as well as capturing the peak action, post-production techniques, shooting in low light, and marketing your images"--Resource description page.